Response of Two Local Rice Cultivars to Different Doses of Nitrogen Fertilizer in Two Paddy Fields - Rusdiansyah, Rusdiansyah; Saleh, Muhammad (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2017)
The study aimed to determine the response of two local rice cultivars subjected to different doses of nitrogen (N) fertilizer in two paddy fields, namely Petung and Gunung Makmur in Penajam Paser Utara, East Kalimantan. The research was arranged in Nested Design with five doses of N fertilizers, two cultivars, and two locations as treatments. The doses of N fertilizers were 0, 25, 50, 75 and 100 kg N.ha-1 nested in two cultivars (Nanung and Pance Kuning) and two locations (Petung and Gunung Makmur). Each treatment was conducted in three replicates. The result showed that the Pance Kuning cultivar was superior than Nanung in Petung location in terms of the number of tillers per hill, number of productive tillers per hill, percentage of filled grain per panicle, weight of 1000 grains and potential yield. A different effect of N fertilizer was observed on the number of tillers per hill, percentage of filled grain per panicle and weight of 1000 grains. Nanung and Pance Kuning showed positive responses to the application of 75 kg N.ha-1 in Petung for the parameters of tiller number and weight of 1000 grains.